La cultura médica instrumental: los viajes políticos de los esfigmógrafos entre Europa y América. - Laura Cházaro (Nuevo mundo - Mundos Nuevos, 2006)
Generally explained by the association between precision and instrument, the instrumental dominion of medicine in actual days is assumed as a natural and necessary destiny. Placed in the practices of Mexican physicians of the XIX century, I discuss this naturalized image of medical instruments. Taking as a case the Sphygmograph, device recorder of the cardiac pulse, I interrogate the reasons of the massive import of instruments from the European markets. I have found that the political search for affirming normality and civilization of the Mexican population encircle an epistemological dimension; the instruments are revealed as appliances of knowledge and objects of consumption, in this case, of the colonial market, which hierarchies determined how in this side of America medical doctors were creating knowledge and instruments importing Europe’s instruments.